Risk factors for stress urinary incontinence following vaginal and caesarean delivery: Faktor-faktor risiko stres inkontinensia urin setelah persalinan pervaginam dan perabdominam - Nur Waqiah; David Lotisna; Nusratuddin Abdullah (Indonesian Socety of Obstetrics and Gynecology, 2019)
Abstract Background: Most of the stress urinary incontinence (SUI) occurs after first delivery and related to the mode of delivery. Objective: To determine the factors that affects the incidence of stress urinary incontinence post partum Methods: Women experienced with stress urinary incontinence 3 months after birth vaginally or section caesarean were enrolled in the present cross sectional study. The strength of the pelvic floor muscle measured with perineometer. All of women were assessed for SUI using Sandvix Severity Index (SSI) dan The three incontinence question (3IQ) questionnaire. A person chi-square test was used to analysis with p value <0.05 was considered significant. Results: Eighty-four women with stress urinary incontinence (SUI) after vaginal delivery or caesarean section enrolled in the study. There was a significant difference between mode of delivery and SUI following delivery (p<0.05). Perineal tear (grade 1-2), BMI, newborn weight and circumference significantly affect the SUI after vaginal or caesarean section. Perineal tear increase SUI after delivery 7-fold compared to other factors (OR=7.367; 95% CI=1.815-29.904). Conclusion : SUI after delivery affected by Mode of delivery, pelvic muscle floor weakness, perineal tear, BMI, newborn weight and head circumference. Keywords: stress urinary incontinence, mode of delivery Abstrak Latar belakang: Sebagian besar kasus stress inkontinensia urin terjadi setelah partus pertama kali dan berhubungan dengan metode persalinan. Tujuan: Untuk mengetahui faktor-faktor yang mempengaruhi terjadinya stress inkontinensia urin post partum Metode: Wanita yang mengalami stres inkontinensia urin 3 bulan postpartum normal atau seksio dilibatkan dalam penelitian cross sectional ini. Kekuatan otot dasar panggul diukur dengan perineometer. Penilaian SUI dilakuakn dengan menggunakan kuesioner Sandvix Severity Index (SSI) dan The three incontinence question (3IQ). Data dianalisis dengan uji Chi-square dengan tingkat kemaknaan p<0,05. Hasil: Delapan puluh empat wanita dengan SIU postpartum per vaginam atau operasi caesar dilibatkan dalam penelitian ini. Terdapat perbedaan signifikan antara cara persalinan dan SIU setelah postpartum (p<0,05). Ruptur perineum (grade 1-2), IMT, berat bayi lahir dan lingkar kepala secara signifikan mempengaruhi SIU postpartum. Ruptur perineum meningkatkan SUI postpartum 7 kali lipat dibandingkan dengan faktor-faktor lainnya (OR = 7,367; 95% CI = 1,815-29,904). Kesimpulan: SIU postpartum dipengaruhi oleh cara persalinan, kelemahan dasar otot panggul, robekan perineum, IMT, berat bayi lahir dan lingkar kepala. Kata kunci : stress inkontinensia urin, metode persalinan